1961
DOI: 10.1149/1.2427953
|View full text |Cite
|
Sign up to set email alerts
|

The DSK System of Fuel Cell Electrodes

Abstract: Double skeleton catalyst (DSK) electrodes combine the high catalytic activity of Raney powder catalysts with the mechanical rigidity and electrical conductivity of bulk metals. They consist of a supporting macroskeleton pressed and sintered of metal grains of uniform size and Raney catalyst grains embedded in its pores. The authors have prepared more than 3000 different samples and investigated the following parameters: composition and particle size of both catalyst and macroskeleton, blending ratio of these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
2

Year Published

1967
1967
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 3 publications
0
15
0
2
Order By: Relevance
“…Several methods have been developed for the collection of electrolyfically evolved gases. In particular, double -5 -' skeleton catalyst electrodes 17 have been used to evolve and collect H2 in aqueous electrolytic media. Another effective approach to gas collection at electrodes in molten salt media is the porous valve electrode described by Swinkels.…”
Section: Recovery Of Tritium From the Saltmentioning
confidence: 99%
“…Several methods have been developed for the collection of electrolyfically evolved gases. In particular, double -5 -' skeleton catalyst electrodes 17 have been used to evolve and collect H2 in aqueous electrolytic media. Another effective approach to gas collection at electrodes in molten salt media is the porous valve electrode described by Swinkels.…”
Section: Recovery Of Tritium From the Saltmentioning
confidence: 99%
“…In the scanning electron microscopy (SEM) image of Raney nickel given in the literature [19], it is shown that Raney nickel is composed of pores arranged in a crisscross pattern with a supporting skeleton. Raney nickel, as a porous material, has found widespread application as a catalyst of hydrogenation of organic compounds [19] and especially as an anode in liquid fuel cell [20]. Xiao et al [21] have used Raney nickel as a template to prepare palladium and silver dendritic nanostructures with the assistance of ultrasonic waves.…”
Section: Introductionmentioning
confidence: 99%
“…17 Doch bleibt die ganze Anstrengung der Produktivitätsförderung an das allmäch-tige und moralische Wohlfahrtskriterium gebunden, die "Glückseligkeit" aller Staatsbürger herzustellen. 18 Indem die Menschen, insbesondere die "Armen", "zum Dienst des gemeinen Wesens, <…> auch zu vielen Tugenden größtentheils (als) unfä-hig" 19 angesehen werden, tritt der Staat paternalistisch als Promotor ihrer Lebensziele und Bedürfnisse auf, die sie unterstelltermaßen selbst, in ihrer Unvollkommenheit, zu erlangen nicht in der Lage sind. In diesem Sinne kann bei Justi von einem "sozialwirtschaftlichen" Systementwurf die Rede sein, der eine Tradition entwirft, die in der "Socialoekonomie" des 19.…”
unclassified
“…Jahrhundert modernisiert wird. Im Unterschied zur Nationalökonomie des 19 25 ist, werden die Menschen, die sich zu einem Staat zusammenschließen, bestrebt sein, damit einen sozialen Raum zu etablieren, der dem Einzelnen möglichst wenige Handlungsbeschränkungen auferlegt. Ferner will sich der einzelne Mensch natürlicherweise selbst erhalten, vermag sich jedoch im Stand der natürlichen Freiheit vor Übergriffen durch Andere nicht ausreichend zu schützen; eine der Erwartungen, die er mit der Staatsbildung verbindet, bezieht sich dementsprechend auf die Produktion des Gutes Sicherheit.…”
unclassified